Teachers of the future: A qualitative study on the research priorities of Master's students at the University of Education, Diocese of Linz (Pedagogical Horizons, 2025)
What are our teachers of the future researching? What topics interest young teachers? The compulsory school pupils in Austrian schools are as diverse as the research interests in empirical educational research. This research project highlights the research interests of young teachers and teacher training students at the University of Education of the Diocese of Linz (PHDL) are identified, thus shedding light on the interface between the career entry of Master's students and their graduation from the PHDL. A qualitative survey examines the research focus of Master's theses by graduates of the University of Education of the Diocese of Linz based on the following question: What are the main research areas of Master's students at the PHDL in their Master's theses and what are the reasons for choosing these research topics? During the survey phase, all Master's thesis proposals and abstracts submitted to the PHDL since 2020 (N = 315) were read and coded. This coding resulted in a comprehensive category system, which was structured using the MAXQDA programme. A focus group setting was then conducted with students from the target group. The results provide insight into the topic selection process for master's theses and the interface between higher education and professional life.